Assessing Hulu Sungai Utara District Poverty Threshold Utilizing the CIBEST Method - Restu Khaliq; Herlita, Jumi; Rahmi Yuningsih puteri (Alhadharah: Jurnal Ilmu Dakwah, 2024)
This research assesses the poverty level in Hulu Sungai Utara District through the CIBEST (Centre of Islamic Business and Economic Studies) framework, which integrates both material and spiritual aspects of poverty. The findings indicate that 60% of families are classified as spiritually wealthy, even though they experience material poverty. However, material poverty continues to be a substantial concern, impacting 34.8% of families. The study highlights the importance of a comprehensive strategy for poverty alleviation that considers both material and spiritual aspects of well-being, as spiritual practices play a vital role in providing psychological and social support but have limited impact on addressing material necessities such as education, healthcare, and income opportunities. Addressing systemic economic challenges, including unequal access to resources, insufficient infrastructure, and income disparities, is crucial for alleviating material poverty. Moreover, implementing gender-sensitive policies is essential for tackling income disparities between male and female respondents across various districts. Integrating these dimensions will enable future poverty alleviation strategies to promote more comprehensive and sustainable development.